International Commercial Law Emerging in Africa - Neels, Jan L (Potchefstroom Electronic Law Journal, 2022)
This article provides an overview of the history of international commercial law in Africa with reference to instruments of the three sister organisations of private international law (in a wide sense): UNCITRAL (the United Nations Commission on International Trade Law), UNIDROIT (the International Institute for the Unification of Private Law) and the HCCH (the Hague Conference on Private International Law). The adoption of UNIDROIT’s Cape Town Convention on International Interests in Mobile Equipment of 2001 is identified as a possible watershed moment in respect of the future development of international commercial law in Africa. Following the creation of an African Continental Free Trade Area by member countries of the African Union, it is suggested that participating states reconsider joining the United Nations Convention on the International Sale of Goods (1980) (CISG) and incorporating the UNCITRAL Model Law on International Commercial Arbitration (1985/2006), which are in a certain sense the two founding documents of the modern lex mercatoria. Another priority, the author suggests, is that Africa needs a supporting instrument on the private international law of contract. The first draft of the African Principles on the Law Applicable to International Commercial Contracts is then discussed with an emphasis on the role of substantive law instruments, in particular the CISG